Stress reactivity during short trauma narratives in adolescents with post-traumatic stress disorder (PTSD) and complex PTSD - Oswald D. Kothgassner; Sarah Macura; Andreas Goreis; Diana Klinger; Bettina Pfeffer; Sofia M. Oehlke; Karin Prillinger; Johanna X. Kafka; Heidi Elisabeth Zesch; Anna Felnhofer; Paul L. Plener (European Journal of Psychotraumatology, 2025)
Background: Psychophysiological dysregulations and negative alterations in cognitions and mood characterize post traumatic stress disorder (PTSD) and complex PTSD (C-PTSD), contributing to an increased risk of disorder persistence and chronic health problems. However, understanding the differences in physiological stress reactivity and negative cognitive-emotional patterns between adolescents with PTSD and C-PTSD remains a notable research gap.Objective: This study examined group differences in autonomic nervous system (ANS) reactivity during the sharing of a short trauma narrative, including resting and recovery phases, and compared subjective experiences of stress, shame, and guilt among adolescents with PTSD, C-PTSD, and trauma-exposed controls.Methods: In a repeated-measures design, 52 adolescents (14–18 years) with PTSD (n = 17), C-PTSD (n = 18), and a control group (n = 17) were assessed for heart rate, heart rate variability, and subjective experiences of stress, shame, and guilt during a standardized trauma interview, as well as during baseline and recovery phases.Results: Linear mixed-effects models revealed a significant interaction between group and time point (F = 4.134, p < .001). The C-PTSD group exhibited a significantly higher heart rate in the recovery phase compared to the PTSD (p = .010) and control groups (p = .036), alongside significantly higher subjective stress, guilt, and shame experiences. Main effects of group were identified for perceived stress (F = 7.543, p = .002), guilt (F = 21.779, p < .001), and shame (F = 19.309, p < .001), with the C-PTSD group exhibiting higher levels compared to PTSD and control groups across all conditions.Conclusions: Prolonged stress responses and elevated experiences of shame and guilt in adolescents with C-PTSD align with the diagnostic criteria of affective dysregulation and negative self-concept. Objective stress measures during trauma interviews may support the diagnosis of C-PTSD. Findings highlight the importance of phase-based trauma therapies that target emotional dysregulation, shame, and guilt.